Inventario acerca de la percepción que tienen los niños y las niñas de las relaciones con sus padres y madres: Version para 4 a 6 años - Richaud de Minzi, Maria Cristina (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Our goal with this research effort was to develop an inventory to assess childrens’ perception of parental behavior in subjects 4 to 6 years-old. Two versions, one for mothers and one for fathers, were administered to 119 pre-school children. The inventory had adequate reliability. The factor structure of the two versions was clear and different psychological theoretical dimensions were established for mother and father that indicated the inventory’s construct validity. The inventory assesses Acceptance, Control and Rejection of both parents; Control and Possessiveness were characteristic of mothers and Coercion and Disinterest of fathers. Lax discipline was perceived as resulting from rejection or disinterest, and rigid discipline was perceived as the result of concern for the others rather than aggression.